Electrochemical impedance spectroscopy of poly(N-methyl pyrrole) on carbon fiber microelectrodes and morphology - Sarac, A.S.; Sezgin, S.; Ates, M.; Turhan, C.M.; Parlak, E.A.; Irfanoglu, B. (Elsevier BV, 2008)
This work reports the supercapacitive properties of electrochemically grown homopolymer films on carbon fiber microelectrode (CFME) via poly(N-methyl pyrrole) (P(NMPy)) which is characterized by cyclic voltammetry (CV), Fourier transform infrared reflectance (attenuated total reflection) spectroscopy (FTIR-ATR), scanning electron microscopy (SEM), atomic force microscopy (AFM) and electrochemical impedance spectroscopy (EIS). Microporosity of P(NMPy) electrocoated carbon fiber microelectrodes facilitated improved capacitance and redox behaviours by applying different DC potentials in electrochemical impedance spectroscopic measurements. The capacitance values of P(NMPy)/CFME is obtained (0.059 F) which is in the range of manufactured values.